2018
DOI: 10.1063/1.5031778
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic exciton theory of singlet fission. III. How vibronic coupling and thermodynamics promote rapid triplet generation in pentacene crystals

Abstract: We extend the vibronic exciton theory introduced in our previous work to study singlet fission dynamics, in particular addressing recent indications of the importance of vibronic coupling in this process. A microscopic and non-perturbative treatment of electronic and selected vibrational degrees of freedom in combination with Redfield theory allows us to dynamically consider clusters of molecules under conditions close to those in molecular crystals that exhibit fission. Using bulk pentacene as a concrete exam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
109
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 56 publications
(142 reference statements)
1
109
0
Order By: Relevance
“…35,39 Experimental signatures of vibrational coherences have been detected using ultrafast vibrational and 2D electronic spectroscopy, where both inter-and intramolecular vibrational modes have been found to be important. [40][41][42][43][44] For incoherent triplet pair formation, the signature of vibrational mediation has been the dependence of the singlet ssion rate constant on the energetic driving force DE S-TT . This driving force increases with n, the number of rings in the oligoacene chromophore, such that tetracene (Tc, n ¼ 4) < pentacene (Pc, n ¼ 5) < hexacene (Hc, n ¼ 6).…”
Section: Introductionmentioning
confidence: 99%
“…35,39 Experimental signatures of vibrational coherences have been detected using ultrafast vibrational and 2D electronic spectroscopy, where both inter-and intramolecular vibrational modes have been found to be important. [40][41][42][43][44] For incoherent triplet pair formation, the signature of vibrational mediation has been the dependence of the singlet ssion rate constant on the energetic driving force DE S-TT . This driving force increases with n, the number of rings in the oligoacene chromophore, such that tetracene (Tc, n ¼ 4) < pentacene (Pc, n ¼ 5) < hexacene (Hc, n ¼ 6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the structural complexity of these systems precluded direct interpretation in terms of specific motions and their role in the reaction. Within the theoretical community, studies have shown that the typical vibronic couplings in singlet fission materials are strong (10’s to 100’s meV) and thus require non-perturbative methods to be accurately described 25,29,30 , and the same is true in many other molecular systems 31 . As a result, advanced simulation techniques have been applied to elucidate the varied roles of ultrafast and non-equilibrium environmental dynamics on fission 3235 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, advanced simulation techniques have been applied to elucidate the varied roles of ultrafast and non-equilibrium environmental dynamics on fission 3235 . There is growing recognition that singlet fission, like the majority of ultrafast (<10 ps) processes, is intimately coupled to nuclear dynamics 23,29,30,3642 . Nonetheless there is no clear determination of what motions drive the process, how this coupling occurs, or indeed whether the reported vibrational coherence is important in achieving a high reaction yield or simply a consequence of the ultrafast nature of the reaction with no functional importance.…”
Section: Introductionmentioning
confidence: 99%
“…In synthetic molecular materials developed for organic electronics they have transformed transistor and lightemitting diode technology [6][7][8] , as well as becoming promising components for next-generation photovoltaic (PV) devices with the potential to overcome the Shockley-Queisser limit via singlet fission (SF). In SF the absorption of a single photon ideally results in the formation of two spatially separated triplet excitons [9][10][11][12] , although a concerted sequence of ultrafast electronic and vibrational dynamics must compete with both radiative and non-radiative losses for this exciton multiplication to be efficient enough for applications [13][14][15][16][17] . Observation, understanding and control of these many-body quantum dynamics is therefore essential for optimisation of conjugated molecules for technologies such as SFenhanced PVs [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%